2007
DOI: 10.1002/cncr.22637
|View full text |Cite
|
Sign up to set email alerts
|

Elevated plasma tissue inhibitor of metalloproteinase‐1 level predicts decreased response and survival in metastatic breast cancer

Abstract: BACKGROUND. Tissue inhibitors of metalloproteinase (TIMPs) have at least 2 different functions. They inhibit the catalytic activity of matrix metalloproteinases, and they act as growth factors. METHODS.Pretreatment ethylenediamine tetracetic acid plasma TIMP-1 was assayed from 251 patients who were enrolled in a Phase III, second-line, hormone therapy trial, and from a control group of 50 healthy, postmenopausal women by using the TIMP-1 enzyme-linked immunosorbent assay. RESULTS.The plasma TIMP-1 levels from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
34
0
3

Year Published

2008
2008
2013
2013

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 29 publications
3
34
0
3
Order By: Relevance
“…Tissue inhibitor of metalloproteinases-1 (TIMP-1) has proven to be a promising marker in breast cancer carrying both prognostic [7][8][9][10][11] and, as shown more recently, predictive information [12][13][14][15]. For example, our laboratory has previously demonstrated that high primary tumor tissue levels of TIMP-1 were significantly associated with a poor response to the most frequently used chemotherapeutic drugs in metastatic breast cancer [14].…”
Section: Introductionmentioning
confidence: 99%
“…Tissue inhibitor of metalloproteinases-1 (TIMP-1) has proven to be a promising marker in breast cancer carrying both prognostic [7][8][9][10][11] and, as shown more recently, predictive information [12][13][14][15]. For example, our laboratory has previously demonstrated that high primary tumor tissue levels of TIMP-1 were significantly associated with a poor response to the most frequently used chemotherapeutic drugs in metastatic breast cancer [14].…”
Section: Introductionmentioning
confidence: 99%
“…The natural-occurring endogenous inhibitor of MMP-9 is tissue inhibitor of metalloproteinase-1 (TIMP-1) (9). Similar to MMPs, the role of TIMPs in cancer is reported contradictory and both tumor-protective and tumor-enhancing properties have been reported (10)(11)(12)(13). In breast cancer patients, high tumor and serum levels of TIMP-1 have been associated with decreased response to chemotherapy and decreased survival, suggesting a detrimental effect of TIMP-1 (14)(15)(16).…”
mentioning
confidence: 99%
“…Níveis altos de MMP e Timp3 estão relacionados com casos de pior prognóstico e maior risco de metástase em câncer de mama (Jinga et al, 2006;Lipton et al, 2007;Vizoso et al, 2007). Obtivemos maior expressão de Timp3 no grupo tamoxifeno em relação ao DMBA (Tabela 8).…”
Section: Discussionunclassified
“…Obtivemos maior expressão de Timp3 no grupo tamoxifeno em relação ao DMBA (Tabela 8). Essa alta expressão de Timp poderia estar relacionada com diminuição da resposta ao tratamento anti-hormonal, comprovando nossos resultados (Lipton et al, 2007).…”
Section: Discussionunclassified
See 1 more Smart Citation